Anomalous slip of ZrB2 ceramic grains during in-situ micropillar compression up to 500 °C. (April 2019) - Csanádi, Tamás; Wehrs, Juri; Grasso, Salvatore; Reece, Mike; Michler, Johann; Dusza, Ján
Abstract: The anisotropic deformation behaviour of ZrB2 grains of basal and prismatic orientations in a polycrystalline ZrB2 sample was studied during in-situ micropillar compression at room temperature (RT), 350 °C and 500 °C. Micropillars were milled out of large grains by focused ion beam machining; the basal and prismatic orientations were previously identified using electron backscatter diffraction maps. The basal pillars showed brittle behaviour and cracking on the 10 1 ¯ 0 and 2 1 ¯ 1 ¯ 0 type prismatic planes that lead to their collapse. For this orientation, the yield/rupture stress ranged between 8 and 14 GPa and it exceeded 12 GPa even at 500 °C. In the prismatic orientation, considerable plasticity was observed, showing a temperature dependent yield stress from 6 to 8 GPa at room temperature to 2GPa at 500 °C. The activated slip system family was identified as 10 1 ¯ 0 11 2 ¯ 3 type for all of the test temperatures (RT, 350 °C and 500 °C). Analysis of the Schmid-factors revealed that the plasticity of the prismatic micropillars is controlled by the temperature dependence of the critical resolved shear stress of the 10 1 ¯ 0 11 2 ¯ 3 slip systems. The brittleness of the basal micropillars was influenced by their defect structure (e.g. microcracks) and it was temperature independent due to the absence of slip activation. Highlights: Anisotropic deformation was observed in ZrB2 micropillars from room temperature to 500°C. Basal pillars showed cracking on the 10 1 ¯ 0 and 2 1 ¯ 1 ¯ 0 type prismatic planes with rupture stress ranged between 8 and 14 GPa. Prismatic pillars exhibited considerable plasticity and temperature dependent yield stress from 6-8 GPa to 2 GPa. The activation of the 10 1 ¯ 0 11 2 ¯ 3 type slip system was identified for all of the test temperatures (RT, 350°C and 500°C).